2000
DOI: 10.1177/070674370004500603
|View full text |Cite
|
Sign up to set email alerts
|

II. Cost-Effectiveness Analysis of Psychiatric Deinstitutionalization

Abstract: Background: The cost-effectiveness of the eventual deinstitutionalization of patients with severe and persistent mental disorders who are currently hospitalized in long-term care remains a controversial matter. Methods A retrospective cohort of 96 pairs of psychiatric hospital patients with 1 member deinstitutionalized between 1989 and 1998 was followed up for nearly 10 years. All use of medical and social services was documented. Patients were evaluated at the start and end of the study on various clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
(1 reference statement)
0
20
0
3
Order By: Relevance
“…Allerdings fehlen bei diesen Analysen Aussagen darüber, in welchem Umfang die dokumentierten Kostenreduzierungen für das gesamte Spektrum schwer erkrankter Patienten repräsentativ sind [27].…”
Section: Analysen Zur Enthospitalisierung Stationärer Langzeitpatientenunclassified
See 2 more Smart Citations
“…Allerdings fehlen bei diesen Analysen Aussagen darüber, in welchem Umfang die dokumentierten Kostenreduzierungen für das gesamte Spektrum schwer erkrankter Patienten repräsentativ sind [27].…”
Section: Analysen Zur Enthospitalisierung Stationärer Langzeitpatientenunclassified
“…Auch für Kanada kommen Reinharz et al [27] im Rahmen einer Kohortenstudie über 10 Jahre zu dem Ergebnis, dass die Kosten einer dauerhaften stationären Versorgung schwer chronisch psychisch kranker Patienten signifikant hö-her liegen als eine ambulante Versorgung, auch wenn für einen Teil der ambulant behandelten Patienten wiederkehrende stationäre Behandlungsepisoden notwendig waren. Auch für diese Studien räu-men die Autoren Einschränkungen der Verallgemeinerungsfähigkeit der Ergebnisse besonders hinsichtlich der Patienten mit einem großen Versorgungsbedarf ein [27].…”
Section: Analysen Zur Enthospitalisierung Stationärer Langzeitpatientenunclassified
See 1 more Smart Citation
“…positive outcomes of deinstitutionalisation: Clinically, community living has been associated with a reduction in psychiatric symptoms, especially psychotic symptoms 8,9,11,15,17 , increased clinical effectiveness 11 , clinical stability 12,21 , and a reduced need for medication. 12 On the social side, community living has been reported to lead to a higher level of social functioning, greater independence, better living skills, and increased employment.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 On the humanistic side, community living fosters patients' human rights18 and quality of life 2,5,[11][12][13]22 , fulfils more of their needs 5 , and patients prefer it. 2,5,[12][13]23 Although some studies have found that community living supported by out-patient psychiatric treatment is cheaper than hospital care 1,9,24 , the opposite has been demonstrated more frequently by others.2 Similarly, there have been conflicting findings on whether or not deinstitutionalisation is associated with an improvement in or worsening of maladaptive behaviour. 22 Following in the wake of international trends, there has been a national drive in South Africa for the deinstitutionalization of longterm psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%